Comparative Central European culture - Tötösy de Zepetnek, Steven, 1950- (Comparative cultural studies., 2002)
Rev. and expanded versions of papers originally presented at three different conferences held during 1999-2000: the 24th annual conference, American Hungarian Educators' Association (Cleveland, 1999); Central European Culture Today (University of Alberta, Edmonton, Sept. 1999); annual conference, Modern Language Association (Washington, D.C., 2000).